KEBUTUHAN KARYAWAN TETAP BERDASARKAN BEBAN KERJA TWOGATHER WEDDING PLANNER BALI PADA MASA PANDEMI - Deyanta, Ni Made Elma Putri Ria; Asmarani, I Gusti Ayu Ratih (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Pariwisata Bali, 2023)
A wedding planner is a service company whose job is to assist and arrange clients' wedding planning. Twogather Wedding Planner Bali has been one of the wedding planner companies in Bali since 2013. In 2019, this company experienced a decreased number of employees and clients due to the impact of the covid-19 pandemic. The reduction in employees resulted in increased workload, so the company's employees were overwhelmed to handle it. At the end of 2021, Twogather Wedding Planner Bali began to carry out a remarketing strategy under different conditions, namely having a makeshift workforce. This study aims to determine the number of operational employees during the pandemic based on workload at Twogather Wedding Planner Bali. The data analysis technique used is descriptive quantitative using Workload Analysis, and Workforce Analysis. Meanwhile, to support this research, interview methods, documentation studies, and observations were applied to obtain the ideal number of operational employees based on the company's workload during the pandemic. The results of this study indicate that the number of operational employees required according to the workload at Twogather Wedding Planner Bali during the pandemic is six people to complete 1,700 minutes of workload per day. But in reality, there are only three operational employees available. The lack of these three people causes an increase in the working hours of operational employees and the psychological burden, which impacts the operational employees' performance.